Hubungan Motivasi Belajar dengan Hasil Belajar Siswa dalam Pembelajaran Renda di SMK N 8 Padang - Mardhatillah, Mardhatillah; Sandra, Yofita (ALSYS, 2025)
This research is motivated by the low motivation of students in learning lace which makes student learning outcomes low. This study aims to see the relationship between learning motivation and student learning outcomes in learning Lace at SMK N 8 Padang.This study uses correlational research. The population in the study were all students majoring in creative craft batik and textiles SMK N 8 Padang as many as 128 students. The sample technique used Purposive Sampling with a sample size of 45 students from class XI. Data collection techniques used were questionnaires that were tested for validity and reliability and documentation. Data were analyzed using product moment correlation data analysis techniques. The results showed that there was a positive relationship between learning motivation and learning outcomes of SMK N 8 Padang students in lace learning with a large relationship rhitung 0.122 and a significant value of 0.424> 0.05. The contribution of learning motivation to learning outcomes is 1.48% in the category of related but very low or very weak correlation. Therefore, the conclusion obtained by the researcher is that there is a weak relationship between learning motivation and student learning outcomes because it is not significantly related to motivation.